Factors Affecting Team Performance - Fadli Illahi; Hesky Junaidi; Hilman Wira; Radiah Hamdah; Ruth Wellerina (Syntax Corporation Indonesia, 2024)
This study aims to determine the influence of Core Self Evaluation, Team Cohesion, Organizational Culture, and Agile Teamwork on Team Performance. This is a descriptive quantitative study with a sample size of 300. Data collection techniques include questionnaires and literature studies, with data analysis using multiple regression analysis. Results, The study shows that Core Self Evaluation, Team Cohesion, Organizational Culture, and Agile Teamwork significantly and positively influence Team Performance. This means the better the Core Self Evaluation, Team Cohesion, Organizational Culture, Agile Teamwork, the higher the Team Performance. Implications, This study can be a reference for organizations in forming policies and reward systems that support aspects of Core Self Evaluation, Team Cohesion, Organizational Culture, Agile Teamwork. Rewards can be given to create a positive culture, increase team cohesion, and support adaptive performance. Originality, The novelty of this study lies in the examination of Core Self Evaluation, Organizational Culture, Agile Teamwork together on team performance, conducted in the Jabodetabek area.